Effect of Different Organic Manures on Growth, Yield, and Quality of Radish (Raphanus Sativus) (SAARC Journal of Agriculture, 2021)
An experiment was conducted to evaluate the influence of different organic manures on growth, yield, and quality of radish (Raphanus sativus) at Institute of Agriculture and Animal Science (IAAS), Rupandehi, Nepal. The experiment was laid in Randomized Complete Block Design single factorial with seven treatments and three replications. The treatments were consisted as farmyard manure (FYM) (30 tha-1), poultry manure (PM) (30 tha-1), FYM(15 tha-1) + PM (15 tha-1), FYM (15 tha-1) + vermin compost (2.5 tha-1) + phosphate solubilizing bacteria (PSB) (10kgha-1), FYM (15 tha-1) + bone meal (5 tha-1) + PSB ( 10 kgha-1), PM (15 tha-1) + vermi compost (2.5 tha-1) + PSB (10 kgha-1), PM (15 tha-1) + bone meal (5 tha-1) + PSB (10 kgha-1). A significant variation was observed among the treatments. The poultry manures combined with bone meal and PSB significantly increased the growth and yield attributes viz., plant height (43.43 cm), number of leaves (20.9), shoot length (44.49 cm), root length (21.68 cm), root diameter (3.77 cm), root weight (211.3 gm plant-1 ), shoot weight (170.9 gm plant-1), biological yield (82.28 gm plant-1), dry root weight (46.89 gm plant-1), dry shoot weight (50.33 gm plant-1), total dry weight (97.22 gm plant-1), root yield (49.31 tha-1), shoot yield (939.87 tha-1) and biological yield (89.19 tha-1) at 70 days after sowing. The vitamin-C in radish root was recorded highest (2.87 mgml-1) with PM. However, the total soluble solid remains unchanged among the treatments. In total, the results suggested that poultry manures combined with bone meal and PSB is suitable to cultivate radish.SAARC J. Agri., 18(2): 101-114 (2020)